2017
DOI: 10.1371/journal.pone.0169585
|View full text |Cite
|
Sign up to set email alerts
|

AT7867 Inhibits Human Colorectal Cancer Cells via AKT-Dependent and AKT-Independent Mechanisms

Abstract: AKT is often hyper-activated in human colorectal cancers (CRC). This current study evaluated the potential anti-CRC activity by AT7867, a novel AKT and p70S6K1 (S6K1) dual inhibitor. We showed that AT7867 inhibited survival and proliferation of established (HT-29, HCT116 and DLD-1 lines) and primary human CRC cells. Meanwhile, it provoked caspase-dependent apoptosis in the CRC cells. Molecularly, AT7867 blocked AKT-S6K1 activation in CRC cells. Restoring AKT-S6K1 activation, via expression of a constitutively-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…A previous study indicated that inhibition of SPHK1 activity by treatment with safingol markedly potentiated epigallocatechin gallate-induced apoptotic activity in vitro and in vivo (32). The results of the present study were consistent with several studies on other cancer types (33)(34)(35). In addition, inhibition of SPHK1 was demonstrated to sensitize TC cells to chemotherapeutic drugs, including 5-fluorouracil, docetaxel, doxorubicin and cisplatin.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study indicated that inhibition of SPHK1 activity by treatment with safingol markedly potentiated epigallocatechin gallate-induced apoptotic activity in vitro and in vivo (32). The results of the present study were consistent with several studies on other cancer types (33)(34)(35). In addition, inhibition of SPHK1 was demonstrated to sensitize TC cells to chemotherapeutic drugs, including 5-fluorouracil, docetaxel, doxorubicin and cisplatin.…”
Section: Discussionsupporting
confidence: 91%
“…As described [ 54 , 55 ], aliquots of 30 μg (per sample) tissue or cell lysates (in RIPA lysis buffer) were electro-transferred to 10-12% SDS-PAGE gel, following by transfer to PVDF membranes. The blots were blocked by 10% milk and were then incubated with designated primary and secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…As described [ 54 ], the female severe combined immunodeficient (SCID) mice (age 4-5 week, weight 18-19 g) were obtained from the Animal Center of Fujian Medical University (Fuzhou, China), and were housed under standard procedures. Animals were randomized into three groups.…”
Section: Methodsmentioning
confidence: 99%
“…PI3K/Akt pathway activation is a recognized mechanism by which colorectal cancer cells resist stress-induced apoptosis (41)(42)(43). We thus sought to determine whether KP metabolites offer protection against apoptosis in colorectal cancer cells.…”
Section: Kyn Protects Colorectal Cancer Cells From Apoptosismentioning
confidence: 99%